The Effect of Company Size and Good Corporate Governance on Profit Management in Automotive Industry Sub Sector Companies and Registered Components on Bei Period 2017 – 2021 - Novien Rialdy (AIBPM Publisher, 2022)
Earnings management practices are common in financial reporting, especially for companies listed on the Indonesia Stock Exchange. This is supported by several examples of cases of earnings management practices which are not aligned on one of the automotive industry and components as occuring at PT. Indomobil Sukses International Tbk and PT Indofarma Tbk. Such cases encourage the researcher to conduct a research on the automotive sub-sector industry and their components. The aim of this study is to obtain empirical evidence about the effect of firm size, and good corporate governance (board of directors, independent directors, audit committee) to earnings management. The populations of this study were 12 companies of sub-sector automotive industry and components listed in Indonesia Stock Exchange. Based on purposive sampling method, the samples obtained were 10 companies that have registered in term of the Indonesia Stock Exchange more than 20 years. Data were obtained from the company's financial statements of automotive industry sub-sector companies and their components of 2017-2021. The hypothesis was tested using multiple linear regression analysis.Keywords: Firm Size, Good Corporate Governance, Profit Management